2009
DOI: 10.1111/j.1744-6570.2009.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conscientiousness and Extraversion on New Labor Market Entrants' Job Search: The Mediating Role of Metacognitive Activities and Positive Emotions

Abstract: Job seekers' Conscientiousness and Extraversion show consistent relationships with their job search activities and success, although the explanatory mechanisms for these relationships are unclear (Kanfer, Wanberg, & Kantrowitz, 2001). To explore these mechanisms, we developed and tested a model in which both Conscientiousness and Extraversion influenced metacognitive activities whereas Extraversion alone influenced positive emotions; these mediating variables in turn were predicted to influence resumé submissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
201
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(220 citation statements)
references
References 39 publications
(73 reference statements)
16
201
1
2
Order By: Relevance
“…It could be that creatine has positive effects on cognitive performance particularly in stressful situations. Positive effects of creatine on cognitive behaviour have been found especially in situations associated with reduced brain creatine, such as sleep deprivation, mild exercise and stressful mathematical tasks (Allen, 2012 Turban et al, 2009). Therefore, apart from Extraversion, these results suggest that higher levels of creatine might be associated with better performance in the labour market.…”
mentioning
confidence: 78%
“…It could be that creatine has positive effects on cognitive performance particularly in stressful situations. Positive effects of creatine on cognitive behaviour have been found especially in situations associated with reduced brain creatine, such as sleep deprivation, mild exercise and stressful mathematical tasks (Allen, 2012 Turban et al, 2009). Therefore, apart from Extraversion, these results suggest that higher levels of creatine might be associated with better performance in the labour market.…”
mentioning
confidence: 78%
“…To obtain a job offer, job seekers usually go through a series of tasks like assessing personal characteristics (e.g., values, needs, abilities), searching job market information, submitting applications, participating in interviews, negotiating with potential employers and making decisions on which job offer to accept (Brown et al, 2006;Wanberg et al, 2010). As university graduates generally have little familiarity with these tasks, job search is often regarded as stressful and full of unexpected difficulties (Turban et al, 2009). Based on career construction theory, we argue that the multiple psychological resources underlying career adaptability promote university graduates' self-regulation capacity in job search, and therefore will increase the likelihood of employment.…”
Section: Career Adaptability and Employment Statusmentioning
confidence: 99%
“…However, the results also showed that job search self-efficacy did not fully Career Adaptability and Job Search Success 18 mediate the relationship between career concern and employment status, as well as the relationship between career control and P-O fit, which suggests the existence of other important mediators in this process. For example, career concern may enable individuals to form meta-cognition to guide the job search process (e.g., Turban et al, 2009), which in turn will predict their employment status. On the other hand, as career control facilitates individuals' being deliberate and organized in making career decisions and transitions, it may relate positively to individuals' job search clarity, which in turn mediates its effects on fit perceptions (Wanberg et al, 2010).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is a long history of the study of organizational attraction and secondly, there is tremendous growth in cross flow of research merge branding concepts from the consumer psychology (Turban et al, 2009) literature of organizational attraction and applicant job search behaviour (Gardner et al, 2010). This merging of employment brand with product and service brands is proficient, simply by recognizing employment as a monetary exchange between workers and employers and also resulting into improved brand equity promotion along with improved recruitment *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%